2022
DOI: 10.1002/ccr3.5817
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis in non‐endemic rural hilly region of Nepal: A case report

Abstract: Visceral leishmaniasis is the most severe form of leishmaniasis, caused by the obligate intracellular protozoan parasites Leishmania donovani or L. infantum , transmitted by the bite of phlebotomine sand fly. Visceral leishmaniasis is a disease of lowlands and uncommon in highlands. We report a case of visceral leishmaniasis in 13‐year‐old female patient from a village of Arghakhanchi situated at an altitude of 1200 m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…There have been reports of VL cases from new focal hilly districts since 2010. 9 11 Some of the studies performed epidemiological, serological, and entomological investigations and confirmed the indigenous transmission of VL in many new foci districts. 7 , 12 …”
Section: Discussionmentioning
confidence: 91%
“…There have been reports of VL cases from new focal hilly districts since 2010. 9 11 Some of the studies performed epidemiological, serological, and entomological investigations and confirmed the indigenous transmission of VL in many new foci districts. 7 , 12 …”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the ratio of secreted IFN-γ to IL-10 was higher in the L. donovani infected macrophages treated with rWnt5A as opposed to the corresponding controls ( Figure 1C ). The gating strategy for ROS+ RAW264.7 macrophages is illustrated in Figure 1D . In view of the anti-parasitic effects of IFN-γ and the pro-parasitic effects of IL-10 (2325), this observation reinforced the antagonistic effect of Wnt5A toward L. donovani infection.…”
Section: Resultsmentioning
confidence: 99%
“…Visceral leishmaniasis (VL) or Kala-azar, caused by infection with the parasite L. donovani turns out fatal if not appropriately treated. While several other drugs such as Amphotericin B and Miltefosine are now used in addition to the traditional antimony drugs to treat VL, the disease still persists in isolated pockets, especially in the rural areas (1)(2)(3). Although not endemic, refractory disease arising from infection with the drug resistant L. donovani strains remains a formidable challenge (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%